SOME CHALLENGES OF COPYRIGHT PROTECTION IN UKRAINE - Рудник, Т. В. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2009)
In this article an author makes research of some copyright protection problems in Ukraine, analyses some deficiencies of legislation, international standards and problems that arise in practice and makes proposals to solve them.